Kelayakan Buku Saku Greening Education untuk Sekolah Menengah Kejuruan - Pratama, Iqbal Kend; Iskandar, Ranu; Naryanto, Rizqi Fitri (Panthera : Jurnal Ilmiah Pendidikan Sains dan Terapan, 2025)
This study aims to develop a pocket book Greening Education as an educational media that supports increasing awareness and implementing environmentally friendly practices at SMK Negeri 1 Puring. This book is compiled based on three main pillars proposed by UNESCO, namely Greening School, Greening Curriculum, and Greening Teacher. The research method used is the 4D development model (Define, Design, Develop, Disseminate), but this study is limited to the development stage due to time and scope limitations. Product validation was carried out by two experts, each from the media and material fields. The validation results showed that the pocket book was included in the feasible category, with an average score of 77.5 from media experts and 70.8 from material experts. Input from the validator, especially highlighted the need for improvements to the cover design and the suitability of the images to the content of the material. Thus, this pocket book is considered to be able to be used as a means of education as well as a promotional media in supporting the Adiwiyata School program and the implementation of Greening Education in the SMK environment. It is hoped that the use of this book can strengthen the integration of sustainability values ​​in the learning process, as well as form a school culture that cares about the environment.